Field of Dreams: Restitution of Pollinator Services in Restored Bird-Pollinated Plant Populations - Frick, K.; Ritchie, Alison; Krauss, S. (2014)
Ecosystem functionality is an increasingly important objective of ecological restoration. Despite this, a few studies have rigorously assessed reproductive functionality within restored plant populations, and it is largely assumed that pollinators follow restoration of plant communities—“build it and they will come.” Here, we applied an ecological genetic approach to determine the impact of spatial separation on mating in Banksia menziesii (Proteaceae), a dominant bird-pollinated species of Banksia woodlands of Western Australia. All plants at three post-mining restored sites (n = 72 [13 years old], n = 21 [8 years old], and n = 20 [9 years old]), as well as a sample from an adjacent natural reference site (n = 42), were genotyped at nine microsatellite loci. Seed set, mating system parameters, realized pollen dispersal through the assignment of paternity to seed, and avian pollinator species composition, abundance and behavior, were assessed. All patches displayed equivalent heterozygosity (He = 0.53–0.59) and very weak genetic divergence (FST ≤ 0.01). Seed of plants within restored sites showed complete outcrossing and relatively high seed set, 26% of which were sired by pollen donors located beyond the local patch. Similar abundance and movement of nectar-feeding birds was observed in restored and natural sites, despite lower bird species diversity in the restored site, where a smaller, less aggressive species was dominant. Our results demonstrate the restitution of wide outcrossing in these restored Banksia patches within an active mine-site, and suggest that restored bird-pollinated Banksia populations are resilient to human impacts, due largely to their generalist pollinator requirements and highly-mobile avian pollinators.